Pengembangan Aplikasi Pencarian Artikel Ilmiah Berbasis Mobile - Gita Purnama, Diki; Mahendra Djuanda, Diaz Ramadhani; Albart, Nicko (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The development of technology and information in the current era of globalization provides many benefits for all sectors, including the world of education. One of them is creating a new innovation by creating a mobile device-based application. Researchers designed a mobile-based journal search application. The purpose of designing this application is to facilitate the academic community in searching for journal references. The location of the research was conducted at Paramadina University with respondents from the entire academic community, namely lecturers and students. The method used in the development of research software is the Waterfall method. Based on the results of the questionnaire given to 50 respondents, it shows that 66% of research reference sources come from general journal articles such as Google Scholar, DOAJ, and Research gate. Thus, an online-based platform that is widely used by respondents to be able to find research reference sources. To be able to provide this solution, the author designed a mobile-based journal search application with an Android base. This is done in order to provide convenience for the academic community in finding sources of journal references. The mobile-based journal article search application can help users find journal articles by using several search options such as keywords, and year of publication.